Analisis Usahatani dan Perhitungan Harga Pokok Produksi Padi Protani di Kecamatan Kemangkon dan Kecamatan Padamara Kabupaten Purbalingga - Rahmah, Adellina Falahiya; Mandamdari, Alpha Nadeira; Sukmaya, Syahrul Ganda (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Inpago Unsoed Protani is resulting from a cross between Ciherang rice and G39 rice which was assembled by a team of plant breeders at Jenderal Soedirman University. Kemangkon District and Padamaran District, Purbalingga Regency are Protani rice producing locations. Protani is still a new variety among farmers, accordingly farming calculations and calculation of the cost of production are needed to know exactly the farming analysis and calculating cost of production. This research aims to determine the costs, revenues, profits, feasibility of Protani rice farming, and calculation of the cost of Protani production. The research was carried out in Kemangkon District and Padamara District, Purbalingga Regency from July to September 2023 with 50 farmers as samples. Data analysis uses profit analysis, Break Even Point analysis, Cost of Income analysis, and cost of production calculation analysis. The research results show that the total costs required for Protani farming per hectare are IDR 20.434.204. The income received from Protani farming per hectare is IDR 32.142.857. The profit received from Protani farming per hectare is IDR 11.708.653. The results of the analysis of the Protani rice farming business during one period show that the farming is feasible to run as seen from the sales results which are to the right of the total cost line with the revenue cost line or are in the profit area or exceed the Break Even Point value and the Revenue Cost value which is more than 1, namely 1,57. The cost of production for Protani is IDR 18.842.622.